Estimation of stature using fragmentary femur and tibia lengths in a Thai population - Ilada Fongkete (2018)
© 2015 Australian Academy of Forensic Sciences. Stature estimation is one of the most important parameters for human identification. The current study aimed to investigate the relationship between stature and femur and tibia measurements other than length in modern Thai skeletons, and to derive regression equations that can be used for living stature estimation when complete bones are unavailable. The sample consisted of 159 males and 96 females. We used two analytical methods, i.e. direct 1-step and indirect 2-step. Results showed that the upper breadth of the femur from males and the maximum anteroposterior diameter of the lateral condyle from females were the best estimators of stature. Maximum proximal breadth of the tibia showed the lowest standard error values in males and females. The derived equations were tested on a holdout sample in which the distal breadth of the tibia exhibited the lowest mean absolute error in both males and females, while in the femur measurements, the maximum anteroposterior diameter of the lateral condyle produced the lowest mean absolute error in males, and an absolute mean value from vertical head diameter in females. The present study suggests that measurements taken from damaged bones can be used for stature estimation.